RELEVANSI KURIKULUM PENDIDIKAN TEKNIK BANGUNAN TERHADAP KOMPETENSI SKKNI GEDUNG DAN MANAJEMEN PELAKSANAAN - Ansheila Rusyda Subiyantari; Abdhy Gazali; Santoso Sri Handoyo; Shilmi Arifah (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
Indonesia's rapidly growing construction industry is a key economic driver, presenting both challenges and opportunities for graduates of the Building Engineering Education Program. Higher education plays a crucial role in developing competent human resources with the relevant knowledge, skills, and expertise to meet industry needs. This study maps the qualifications of technicians and analysts based on the Indonesian National Work Competency Standards (SKKNI) in the construction sector and analyzes the alignment of competency units with Building Engineering Education State University of Jakarta course outcomes. The analysis of SKKNI data from 2024 found that out of 71 job levels in the building subclassification, 14 are for technicians or analysts at KKNI levels 4 to 6, but only 10 have detailed SKKNI documents. In the construction management classification, there are 39 job levels, with 16 for technicians/analysts, all with detailed SKKNI documents. The analysis indicates that 11 job levels are relevant to Building Engineering Education course outcomes, while two are not. Specifically, several job levels in both subclassifications are rated from Relevant to Very Relevant. To address curriculum gaps, recommendations include strengthening the existing curriculum and adding new courses. This study aims to provide a foundation for curriculum revitalization, ensuring Building Engineering Education graduates are competitive in the labor market and meet the evolving needs of the construction industry.